Efficacy of chlorhexidine and green tea mouthwashes in the management of dental plaque-induced gingivitis: A comparative clinical study - Meena B Priya; V Anitha; M Shanmugam; B Ashwath; Suganthi D Sylva; S K Vigneshwari (Wolters Kluwer Medknow Publications, 2015)
Background: The intake of green tea has been increased recently due to its medicinal values. The antibacterial and antioxidant properties of green tea were found to be beneficial in the treatment of gingival and periodontal diseases. The aim of this comparative study was to compare the efficacy of the mouthwash containing green tea and chlorhexidine in the management of dental plaque-induced gingivitis. Materials and Methods: Thirty patients who participated in the study were divided randomly into two groups, each group of 15 patients was prescribed with either chlorhexidine or green tea mouthwash. Turesky modification of Quigley-Hein plaque index, Löe and Silness gingival index, Ainamo and Bay bleeding index, tooth stain, and tongue stain (TS) were recorded at baseline, 15 days, and 1 month. The subjects were asked to report any discomfort or alteration in taste. Results: There was a significant decrease in plaque index, gingival index, and bleeding index in both the groups. However, green tea mouthwash resulted in a statistically significant decrease in bleeding index compared to chlorhexidine group. There was no significant difference in tooth stain and TS in both the groups. Conclusion: The green tea-containing mouthwash is equally effective in reducing the gingival inflammation and plaque to chlorhexidine.